Michaelangelo artist and man - Friedman, Adam; Markham, Monte (New York New Video Group, 1994)
He is one of the greatest artist of all time, a man whose name has become synonymous with the word "masterpiece": Michaelangelo Buonarotti.
With 1 converted disc.
Executive producer, Stuart B. Rekant ; A&E Programming Executive, Michael Cascio
Narrator, Monte Markham
VHS format.
In English.
Keywords: Michaelangelo Bounarroti -- 1475-1564.